Understanding the epidemiology and perceived efficacy of cannabis use in patients with chronic musculoskeletal pain - Timothy Leroux; Prabjit Ajrawat; Kala Sundararajan; Naomi Maldonado-Rodriguez; Bheeshma Ravi; Rajiv Gandhi; Raja Rampersaud; Christian Veillette; Nizar Mahomed; Hance Clarke (BMC, 2024)
Abstract Background The belief that cannabis has analgesic and anti-inflammatory properties continues to attract patients with chronic musculoskeletal (MSK) pain towards its use. However, the role that cannabis will play in the management of chronic MSK pain remains to be determined. This study examined 1) the rate, patterns of use, and self-reported efficacy of cannabis use among patients with chronic MSK pain and 2) the interest and potential barriers to cannabis use among patients with chronic MSK pain not currently using cannabis. Methods Self-reported cannabis use and perceived efficacy were prospectively collected from chronic MSK pain patients presenting to the Orthopaedic Clinic at the University Health Network, Toronto, Canada. The primary dependent variable was current or past use of cannabis to manage chronic MSK pain; bivariate and multivariable logistic regression were used to identify patient characteristics independently associated with this outcome. Secondary outcomes were summarized descriptively, including self-perceived efficacy among cannabis users, and interest as well as barriers to cannabis use among cannabis non-users. Results The sample included 629 patients presenting with chronic MSK pain (mean age: 56±15.7 years; 56% female). Overall, 144 (23%) reported past or present cannabis use to manage their MSK pain, with 63.7% perceiving cannabis as very or somewhat effective and 26.6% considering it as slightly effective. The strongest predictor of cannabis use in this study population was a history of recreational cannabis use (OR 12.7, p<0.001). Among cannabis non-users (N=489), 65% expressed interest in using cannabis to manage their chronic MSK pain, but common barriers to use included lack of knowledge regarding access, use and evidence, and stigma. Conclusions One in five patients presenting to an orthopaedic surgeon with chronic MSK pain are using or have used cannabis with the specific intent to manage their pain, and most report it to be effective. Among non-users, two-thirds reported an interest in using cannabis to manage their MSK pain, but common barriers to use existed. Future double-blind placebo-controlled trials are required to understand if this reported efficacy is accurate, and what role, if any, cannabis may play in the management of chronic MSK pain.